Analisis Efisiensi, Efektivitas dan Akuntabilitas Pengelolaan Sumber Dana Lembaga keuangan Mikro Syari’ah (Studi Kasus di BMT Al-Hasan Mitra Ummat) - Hadratullah; Jiranah, Siti (Al-Qardhu, 2024)
This research is motivated by the Islamic Microfinance Institutions which have experienced quite rapid development. BMT as an Islamic microfinance institution has developed. This development is marked by the increasing number of BMTs and the associations that support them. BMTs can carry out various types of business activities, both related to finance and non-finance. First, the collection of zakat, infaq, and shadaqah funds to be distributed to mustahiq (zakat recipients). Second, the collection of BMT funds by mobilizing funds and developing them in various savings. Third, the distribution of funds through micro and small business financing activities. The purpose of this study is to analyze the level of efficiency, effectiveness, and accountability of the management of Islamic microfinance institution funding sources at BMT Al-Hasan Mitra Ummat. The method used is field research with a Qualitative approach. Field research is where research whose data and information are obtained from activities in the research field directly from the research object. Data analysis used in this study is by collecting data through financial reports at BMT Al-Hasan Mitra Ummat from the period 2018-2020.